Toward sustainable climate change adaptation. (30th January 2020) - Yang, Yi; Liu, Beibei; Wang, Peng; Chen, Wei‐Qiang; Smith, Timothy M.
Abstract: Industrial ecology (IE) has made great contributions to climate change mitigation research, in terms of its systems thinking and solid methodologies such as life cycle assessment, material flow analysis, and environmentally extended input–output analysis. However, its potential contribution to climate change adaptation is unclear. Adaptation has become increasingly urgent in a continuously changing climate, especially in developing countries, which are projected to bear the brunt of climate‐change‐related damages. On the basis of a brief review of climate change impacts and adaptation literature, we suggest that IE can play an important role in the following two aspects. First, with the emphasis on a systems perspective, IE can help us determine how climate change interacts with our socio‐economic system and how the interactions may aggravate (or moderate) its direct impacts or whether they may shift burden to other environmental impacts. Second, IE methodologies can help us quantify the direct and indirect environmental impacts of adaptation activities, identify mitigation opportunities, and achieve sustainable adaptation. Further, we find that substantial investment is needed to increase the resilience of infrastructure (e.g., transport, energy, and water supply) and agriculture in developing countries. Because these sectors are also the main drivers of environmental degradation, how to achieve sustainable climate‐resilient infrastructure and agriculture in developing countries deserves special attention in future IE studies. Overall, IE thinking and methodologies have great potential to contribute to climate change adaptation research and policy questions, and exploring this growing field will, in turn, inspire IE development.